An analysis of the potential implementation of art and music visa as a means to enhance national appeal - Gibran, Atsil Syah; Ardiansyah, Andika; R, Andi Aslam (Polteknik Imigrasi, 2024)
This study analyzes the potential implementation of an Art and Music Visa as a tool to enhance Indonesia's national appeal by strengthening the art and music sectors. Considering the significant contribution of the creative economy sector to the national Gross Domestic Product (GDP), this specialized visa policy is expected to attract international artists and musicians to work in Indonesia, enriching the local creative ecosystem and expanding the reach of Indonesian art and music to global markets. Using a qualitative approach, this study explores the perceptions, needs, and challenges faced by industry stakeholders regarding the proposed visa policy. The SWOT analysis indicates that while the policy holds substantial potential to support the growth of the creative economy, it faces challenges such as complex bureaucratic procedures and competition from more competitive neighboring countries. This research provides evidence-based policy recommendations to support the development of the art and music sectors in Indonesia, while also enhancing national branding as a global hub for arts and culture.